Nursing managers' perceptions of teamwork and collaboration in mining primary healthcare clinics in Gauteng - Sanele E. Nene (AOSIS, 2024)
Background: Teamwork and collaboration among nursing managers, nurses, doctors and peripheral hospitals treating mining patients is pivotal. A case study of specific mining primary healthcare clinics revealed a lack of teamwork among the doctors and nursing managers, even on decisions that show productivity. Objectives: The aim of this study was to explore and describe nursing managers' perceptions of teamwork and collaboration in mining primary healthcare clinics in Gauteng. Method: A qualitative, exploratory, descriptive and contextual research design was adopted to conduct this study. Data were collected by conducting semi-structured individual interviews with 10 participants and thematically analysed. Data saturation was reached by the seventh participant and confirmed with three more interviews. Trustworthiness measures and ethical considerations were preserved as protocols because of the nature of the study. Results: Three themes emanated from the study: (1) team coordination and support improve teamwork and collaboration in primary healthcare clinics, (2) there is a lack of involvement from the nursing team, negatively influencing teamwork and collaboration and (3) collaboration can improve the quality of healthcare services rendered in mining primary healthcare clinics. Conclusion: All mining primary healthcare clinic team members should be involved in operational activities to foster teamwork and collaboration. Contribution: This study revealed that teamwork and collaboration should be facilitated to improve the quality of healthcare service in mining primary healthcare clinics.